Teenagers’ Addiction to Social Networks on the Internet - Bacys, Tomas (Socialinė teorija, empirija, politika ir praktika, 2013)
Summary Social networks are rapidly progressing means of information circulation. It is noticeable that social networks are a centre of attraction for teenagers. The frequent and long login to social networks develops into addiction. The aim of this research has been to reveal how teenagers’ behaviour is influenced by social networks. To achieve this aim, quantitative analysis and theoretical, empirical methods were applied. During the investigation, it has been revealed that teenagers’ behaviour is influenced by social networks. Although the majority of teenagers claim that they are not addicted to social networks, however, addiction to social networks manifests itself psychologically, socially and, to a lesser extent, physiologically. Consequently, the teenagers’ behaviour is dependent on social networks. Key words: teenagers, addiction, social networks on the internet.